Stylistics Analysis Of Anies Baswedan’s Speech - Vaniar Nasininta Nainggolan (Indonesian Journal of Education and Mathematical Science, 2021)
Stylistics is the study of varieties of language. It tries to establish principles capable of accounting for the particular choices made by individuals and social groups in their use of language. This research tried to analyze about stylistics in speech. The objectives of this research to investigate the types of stylistics were used it on video of Anies Baswedan’s speech. To find out the most dominant types stylistics in Anies Baswedan’s speech. In this research used descriptive qualitative methods was be designed by applying descriptive phenomenon design. So, the writer used documentation method to collect the data. The researcher took a full of the total Anies Baswedan’s performed on the video Anies Baswedan speech. From the analysis of the data, the researcher finds five types of stylistics  found in Anies baswedan’s speech when talked about Jakarta marketing week 2019. There were five types of stylistics that analyzed from on the video of Anies Baswedan speech. They were General, Literary, Textualist, Interpretative and Expressive. The percentage of total stylistics on the video, where General was 23.81%, Literary was 19.05 %, Textualist was 23.81 %, Interpretative was 14.28 %, Expressive was 19.05%. on the video of Anies Baswedan’s Speech.